3, 2, 1 and stop! An innovative, straightforward and clean route for the flash synthesis of metallacarboranes. Issue 8 (26th March 2019) - Bennour, Ines; Cioran, Ana M.; Teixidor, Francesc; Viñas, Clara
Abstract : Analogs to metallocene can be synthesised in high yield by heating solids [HNMe3 ][C2 B9 H12 ]/CoCl2 · x H2 O to high temperature for very short time. Abstract : [Co(C2 B9 H11 )2 ] −, analogs to metallocene, can be readily synthesised in high yield by a fast and clean solvent-free reaction of [HNMe3 ][C2 B9 H12 ] with CoCl2 · x H2 O. This innovative approach, applied to both ortho and meta isomers, yields the desired structures by simply heating the solid compounds to high temperature for a very short time.